2016
DOI: 10.2319/122715-892.1
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics for the assessment of upper airway changes in skeletal Class III patients treated with mandibular setback surgery

Abstract: Following mandibular setback surgery, pharyngeal airway volume was decreased and relative mean negative pressure was increased, implying an increased effort required from a patient for maintaining constant pharyngeal airflow. Thus, high-risk patients undergoing a large amount of mandibular setback surgery should be evaluated for obstructive sleep apnea and the proposed treatment plan be revised based on the risk for potential airway compromise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
(36 reference statements)
3
21
0
Order By: Relevance
“…The mean Reynolds numbers without MAD-with MAD at the inlet are (1588-1358) and, in the minimum cross-sectional area in the velopharynx are (2625-1844). These values corresponded to that observed in the literature 23,25,26 . Moreover, the values of mean maximum velocity magnitudes at the minimum cross-sectional area without and with MAD are (7.08-4.21) m/s, aligned well with those reported in other computational studies 23,26 .…”
Section: Flow Characteristics Flow Characteristics Are Summarized Insupporting
confidence: 91%
“…The mean Reynolds numbers without MAD-with MAD at the inlet are (1588-1358) and, in the minimum cross-sectional area in the velopharynx are (2625-1844). These values corresponded to that observed in the literature 23,25,26 . Moreover, the values of mean maximum velocity magnitudes at the minimum cross-sectional area without and with MAD are (7.08-4.21) m/s, aligned well with those reported in other computational studies 23,26 .…”
Section: Flow Characteristics Flow Characteristics Are Summarized Insupporting
confidence: 91%
“…To apply CFD simulation to such a "flabby" organ, it was reconstructed into a simple shape. CFD simulation applied to the reconstructed airway was helpful in effectively analyzing the airflow pattern according to the individual patient's airway type [10,11,25,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…CFD simulation applied to the reconstructed airway was helpful in effectively analyzing the airflow pattern according to the individual patient's airway type. [10,11,25,27,28] Analysis revealed that the velopharynx at T1 was narrowed, but the oropharynx was rather widened. This is assumed to be a result of the upward movement of the maxillomandibular complex because the position of the hyoid bone did not change immediately after the operation, and the distance from the mandible was increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational fluid dynamics studies have been applied to model the flow field and pressure drop in the UA in SAHS using patient specific geometrical models obtained from medical imaging. These studies have allowed the understanding of the flow characteristics in the UA after a pharyngeal surgery [9] [16] [10] [14] and to determinate treatment response using MAD [15] [12] [13]. In [15] [13] studies combining CFD and medical imaging found a strong correlation between change in airway resistance with and without MAD.…”
Section: Introductionmentioning
confidence: 99%